A Lean Enterprise Architecture Approach as an Enabler for Organizational Agility : Case: Metso Outotec - Kapella, Oscar (My University, 2021)
In the era where delivery speed is perceived more important than IT landscape integration, consistency and long-term planning, different architectural approaches have become important considerations of information systems management. Moreover, recent studies have shown that the need for a holistic EA is often overlooked, when organizations try to apply agile development models, which may lead to several problems, such as technical debt, redundant rework, inconsistent communication, decentralized and siloed architecture design, unsustainable architecture, and inconsistence in coding style. Hence, with the growing deployment of scaling agile methods there is a need for purpose-fit approaches to integrate EA frameworks to enable organization agility while maintaining long-term vision. This study aims to explore how EA activities are put into practices in a company deploying large-scale agile development methods – namely EA deliverables, EA benefits, EA concerns and EA enablers. In total, 13 semi-structured interviews were conducted from a case company, and an analysis was done using the Gioia method. As a result, EA deliverables (business objective deliverables, intentional architecture deliverables, and emergent design deliverables), EA benefits (organizational agility and organizational robustness), EA concerns (immaturity, disengagement, urgency, and resistance and anti-patterns), and EA enablers (communication and collaboration, Lean EA, and EA culture) were identified. The enterprise architecture practices used by the case company were in line with the guidelines and best practices recommended by the literature and industry experts. Moreover, a literature review provided some theoretical constructs and suggestions, namely the Lean EA development (LEAD) method and the design principles of architectural thinking for supporting organizational agility, which can be recommended to be applied by the case company or any other organization scaling agile.
Keywords: lean enterprise architecture, large-scale agile development, organizational agility